1995
DOI: 10.1021/jf00057a025
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Constituents of Soybean [Glycine max (L.) Merril] Milk Lacking Lipoxygenase Isoenzymes

Abstract: The soybean milk odor of samples lacking lipoxygenases (LOs) 2 and 3 and LOs 1, 2, and 3, was concentrated by simultaneous distillation and extraction (SDE), together with that of normal soybean milk. The constituents of the odorants were identified by GC and GC-MS data. The yields of volatile compounds were greatly decreased when the lipoxygenases were lacking, and the changes of each constituent were discussed. From the aroma extract dilution analysis, the Cg, Cg, and Cio alcohols and carbonyl compounds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 12 publications
6
105
1
1
Order By: Relevance
“…They concluded that the main odor contributors were trans,trans-2,4-nonadienal, trans,trans-2,4-decadienal, hexanal, 2-pentyl furan, 1-octen-3-one, trans-2-nonenal, trans, cis-2,4-nonadienal, and an unidentified compound. The distillation method used by Kobayashi et al (15) could not have detected methanethiol, acetaldehyde, or any other volatile compound that had a boiling point below that of ethyl ether (35°C). Also, because soymilk sold in the United States, and most of the world, is typically heated (blanched)-to deactivate the LOX, other degradative enzymes, and trypsin inhibitors-and subsequently pasteurized, research on unblanched soymilk (and soybean slurries) has limited application.…”
mentioning
confidence: 96%
“…They concluded that the main odor contributors were trans,trans-2,4-nonadienal, trans,trans-2,4-decadienal, hexanal, 2-pentyl furan, 1-octen-3-one, trans-2-nonenal, trans, cis-2,4-nonadienal, and an unidentified compound. The distillation method used by Kobayashi et al (15) could not have detected methanethiol, acetaldehyde, or any other volatile compound that had a boiling point below that of ethyl ether (35°C). Also, because soymilk sold in the United States, and most of the world, is typically heated (blanched)-to deactivate the LOX, other degradative enzymes, and trypsin inhibitors-and subsequently pasteurized, research on unblanched soymilk (and soybean slurries) has limited application.…”
mentioning
confidence: 96%
“…Almost the same amount of 1-octen-3-ol was found with Fukuyutaka and L-Star because it was formed independently on LOXs. 2,13) Because the homogenate was heated to 80 C in order to facilitate vaporization of volatiles during headspace sampling, it was anticipated that heat degradation of some nonvolatile compounds (such as lipid hydroperoxides) might result in overestimation of the amounts of volatiles. Because heat degradation of hydroperoxides can be largely prevented by the addition of lipophilic antioxidants, we evaluated the effects of the addition of butylated hydroxytoluene.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of 1-octen-3-ol was constant among the soybeans used here, as reported previously. 9) When the seeds were homogenized with a saturated CaCl 2 solution in order to immediately inactivate most enzymes, hardly any of the C6 compounds and 1-octen-3-ol were formed, indicating that they were enzymatically formed after homogenization. When L 123 seeds were homogenized in the presence of the lipoxygenase inhibitor, nordihydroguaiaretic acid, there was little formation of C6-compounds, although the amount of 1-octen-3-ol formed was little affected by the inhibitor (data not shown).…”
Section: Fig 2 Amounts Of Volatiles Emitted From Crude Homogenatesmentioning
confidence: 98%